Awareness of predatory open access journals among academics of the Faculty of Management and Business Studies at the University of Jaffna - Janen, T.; Murugathas, K.; Kupeshan, R. (University of Jaffna, 2022)
Open Access (OA) is a model for publishing scholarly peer-reviewed journals, and articles can be freely read, as the publishing is funded through the Article Pro cessing Charges (APC) other than subscription. The development of open access publishing created a pathway for predatory publishing, which is an exploitive profit-making academic business, charging publication fees from authors without providing quality editorial service. The issue becomes a serious problem for the researchers to differentiate a legitimate publication from a predatory publication. This article aims to measure the awareness of predatory open-access journals among academics. The population of the study was permanent academic staff members attached to the Faculty of Management and Business Studies, University of Jaffna. There was a total of 52 academic staff members, so there was no sampling; all staff members were included in the study. A pretested online questionnaire was circulated among academics from the Faculty of Management and Business Studies, Univer sity of Jaffna. Among the total(n=52) population, 67.3% of the staff responded to the questionnaire. The results of this study revealed that 22.85% of the staff were fully knowledgeable about the open-access system, 40% knowledgeable, 25.71% somewhat knowledgeable, and 11.42% slightly knowledgeable. Faculty members prioritized the listed factors considered during the journal selection, such as duration of the publication process, impact factor, the peer review process, quality of the editorial board, publication costs, editorial support, and journal indexing. Weight score calculated based on the preference level and Journal indexing (209) was highly prioritized by the respondents, followed by the impact factor (179), publication cost (177), and peer review process (168) in journal selection. Nearly 70% of the study participants know about predatory publishing, and 28.5% of the respondents may have heard about it, but they were not sure about predatory publications. Among the respondents, all were aware of at least any systems to differentiate the predatory journal from the legitimate journal. The study suggests that there is a need to conduct more awareness programs to educate the predatory open-access publications to the academic staff members of the Faculty of Management and Business Studies of the University of Jaffna.
Keywords: Open access publishing; Predatory publishing; Journal selection; Legitimate journal